THE EFFECT OF INTERPERSONAL COMMUNICATION AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT FAMILY SEJATI ABADI, BANDUNG REGENCY - Taty Siti Aisah; Tina Aurelia (Universitas Pasundan, 2026)
The textile industry in Bandung Regency plays a strategic role in supporting the regional economy through employment absorption and export contribution. However, intense competition among textile companies demands continuous improvement in employee performance. PT. Family Sejati Abadi, as one of the textile companies in the region, has experienced a decline in performance over the past five years, reflected in reduced productivity and work quality. This decline is suspected to be influenced by poor interpersonal communication and an unbalanced compensation system that does not fully reflect employee contributions. This study aims to determine the effect of interpersonal communication and compensation on employee performance at PT. Eternal True Family. The research method used is descriptive and verification with a quantitative approach. Data were collected through questionnaires distributed via Google Forms, with responses measured using a Likert scale. Sampling was conducted using a non-probability sampling technique with the Slovin formula to determine the number of respondents. Data analysis included validity and reliability testing, path analysis, and hypothesis testing using SPSS version 25 software. The results show that interpersonal communication and compensation have a significant effect on employee performance, both partially and simultaneously. Effective communication between leaders and employees fosters better understanding and coordination, while fair compensation increases motivation, job satisfaction, and commitment. Therefore, companies need to strengthen two-way communication and ensure equitable compensation systems to optimize employee performance and maintain competitiveness within the dynamic textile industry environment. The findings of this research are expected to serve as a reference for management in formulating policies related to human resource development. Future research could explore other factors such as leadership style, work environment, or organizational culture that may also influence employee performance in the textile industry context.